Implementasi Kebijakan PP No 11 Tahun 2021 Pasal 4 Tentang Pengelolaan BUMDesa Di Desa Citaman Jernih Kecamatan Perbaungan Kabupaten Serdang Bedagai Provinsi Sumatera Utara - Amas Mashudin; R. Hamdani Harahap; Budi Hartono (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the imImplementation of PP Policy no 11 of 2021 article 4 regarding the management of Bumdes in Citaman Jernih Village, Perbaungan Sub-District, Serdang Bedagai District, North Sumatra Province using qualitative methods. The research instrument is the researcher himself with the informants selected purposively. Data collection techniques are carried out in three ways through: observation, interviews, and documentation which are commonly used in qualitative research. The results of the study using standard indicators and policy objectives, rewsources, inter-organizational realtionships, characteristics of implementing agents, sosial, economic and political environment and disposition of implementors, show that the implementation of PP Policy No 11 of 2021 article 4 on the management of Bumdes in Citaman Jernih Village Sub-district Perbaungan Serdang Bedagai District North Sumtra Province is not yet optimal. As for the factors that influence the implementation of PP No 11 of 2021 article 4 regarding the management of Bumdes at the research locus, they area resources, inter-organizational relationships, and the characteristics of implementing agents. In the end, the implementation of the policy that has not been optimal has caused the effectiveness of the Bumdesa Management not to meet the stated objectives.